2008
DOI: 10.1158/0008-5472.can-08-1983
|View full text |Cite
|
Sign up to set email alerts
|

Timosaponin A-III Induces Autophagy Preceding Mitochondria-Mediated Apoptosis in HeLa Cancer Cells

Abstract: Timosaponin A-III (TAIII), a saponin isolated from the rhizome of Anemarrhena asphodeloides, exhibits potent cytotoxicity and has the potential to be developed as an anticancer agent. Here, we provide evidence that TAIII induces autophagy in HeLa cells followed by apoptotic cell death. TAIII-induced autophagy was morphologically characterized by the formation of membrane-bound autophagic vacuoles recognizable at the ultrastructural level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 44 publications
11
93
1
1
Order By: Relevance
“…Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo. Further functional analysis showed that inhibition of autophagy markedly increased quercetin-induced apoptotic cell death, suggesting that quercetin-induced autophagy plays a protective role in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo. Further functional analysis showed that inhibition of autophagy markedly increased quercetin-induced apoptotic cell death, suggesting that quercetin-induced autophagy plays a protective role in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 59%
“…Accumulating evidence suggested a paradoxical role of autophagy in control of cell death and survival under various stimulus conditions. [31][32][33][34][35][36] To determine the in the cytoplasm of both AGS and MKN28 cells treated with quercetin. To further characterize the membrane-associated vacuoles, acridine orange staining was used to analyze the formation of acidic vesicular organelles (AVOs), a main feature of autophagy.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…5,6 In some studies, autophagy and apoptosis have been found to exert similar levels of toxicity 7,8 while in others a blockade to protective autophagy has resulted in cytotoxicity due to apoptosis. 3,[9][10][11][12] Finally, a recent report presents evidence for apoptosis that is dependent on prior autophagy. The transient arrest and renewed tumor growth that has been interpreted as tumor dormancy by Lu et al 2 is also a common observation in other xenograft models treated with chemotherapy or radiation; 19,20 our own studies in cell culture [21][22][23] also support the concept of drug and radiation induced senescence in tumor cells that is succeeded by proliferative recovery.…”
Section: Cytoprotective and Cytotoxic Functions Of Autophagymentioning
confidence: 96%
“…Autophagy is a mode of cell death distinct from necrosis and apoptosis. Autophagy is usually considered to be a genetically programmed cell death involving the degradation of cellular proteins and organelles often accompanied by the formation of an autophagosome (20,21). In the process of autophagy, cytoplasmic components such as mitochondria and peroxisomes are encapsulated by an isolation membrane to cause the formation of an autophagosome (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In the process of autophagy, cytoplasmic components such as mitochondria and peroxisomes are encapsulated by an isolation membrane to cause the formation of an autophagosome (20,21). Increasing evidence shows that the autophagic and apoptotic pathways may be regulated by common factors (21,22). Mitochondria are regarded as an important convergent point of apoptotic and autophagic signals, which initiate apoptotic and autophagic cell death (23).…”
Section: Discussionmentioning
confidence: 99%